Anthropic Stressors and Impacts in Pampean Lakes - Menone, Mirta Luján; Pérez, Débora Jesabel; Iturburu, Fernando Gastón (Springer, 2025)
The Pampa region is home to a large part of Argentina’s human population and concentrates a wide variety of productive activities that release chemicals into the environment. Pampean lakes (natural and man-made reservoirs) are subject to different chemical impacts. This chapter is a review of the current sources, both point and diffuse, and chemical pollution detected in the field, from Northern and Southern Pampean lakes. The cited literature is a compilation of original articles published during the last 26 years. The main types of contaminants detected in surface water, sediments and biota are pesticides, polychlorinated biphenyls, polybrominated diphenyl ethers, pharmaceutical and personal care products, hormones, polycyclic aromatic hydrocarbons, metals, metalloids and cyanotoxins. In addition to the description of pollutants found in several environmental matrices (surface water, sediment, biota), we have identified a biomonitor species; the fish Odondesthes bonariensis. Ecological risk assessment (ERA)—the process that evaluates the likelihood that adverse ecological effects may occur or are occurring because of exposure to one or more agents- have been only carried out in a retrospective for pesticides. Finally, we have identified some gaps of knowledge regarding chemical pollution that led to a final recommendation concerning the maintenance of healthy aquatic ecosystems.